Work Intensification and Quality Assurance: Missed Nursing Care. Issue 2 (April 2018) - Willis, Eileen; Harvey, Clare; Thompson, Shona; Pearson, Maria; Meyer, Alannah
Abstract : This article examines nurses' commentaries from a survey conducted in New Zealand that studied contradictions between quality assurance and work intensification in nursing care. Nurse managers were blamed for either avoiding or not recognizing work intensification affecting quality care delivery. However, the data illustrate key structural issues resulting in missed care that impact on patient safety, rather than a problem directly attributable to managers. Until these structural issues are addressed, missed care and adverse events will continue to affect the quality of care. Abstract : Supplemental Digital Content is Available in the Text.